ENVIRONMENT AND SUSTAINABILITY: CHALLENGES AND OPPORTUNITIES OF GLOBAL AND NATIONAL CARBON MARKETS - de Giorge Cerqueira, Homero (Revista Gênero e Interdisciplinaridade, 2025)
This article presents the challenges and opportunities of global and national carbon markets, as well as a study on the Quito Protocol (KP), the Paris Agreement (PA) and the Glasgow – United Nations Conference on Climate Change (COP-26). As a methodology, this article involves a qualitative, descriptive research, with the performance of a documentary research, through the analysis of documents, as well as bibliographical research in national and foreign doctrine, to cross-reference the data for interpretation, supporting the study.